Serum vitamin D (25OHD3) levels and the risk of different subtypes of breast cancer: A nested case–control study. (August 2016) - Shirazi, L.; Almquist, M.; Borgquist, S.; Malm, J.; Manjer, J.
Abstract: Background: Previous studies regarding the association between serum 25-hydroxyvitamin D (25OHD3 ) and breast cancer risk have not been conclusive. The aim of this study was to investigate the potential association between pre-diagnostic serum 25OHD3 levels and the risk of different subtypes of breast cancer. Materials and methods: The study was based on The Malmö Diet and Cancer Study recruiting 17, 035 women from 1991 to 1996. A total of 764 incident breast cancers with matched controls were analysed for 25OHD3 in samples collected at baseline, before diagnosis. A logistic regression analysis was used to calculate odds ratios with 95% confidence intervals for tertiles of 25OHD3 in relation to different subtypes of breast cancer, i.e. defined according to tumour type, tumour size, lymph node involvement, histological grade, oestrogen receptor (ER) status, progesterone receptor (PgR) status, Ki67, cyclin D1 and p27. Results: As compared to the 1st tertile of 25OHD3, the second tertile had a statistically significantly lower risk of ER negative tumours, PgR negative tumours and tumours with a high expression of Ki67, A similar pattern was seen in relation to large tumours (≥21 mm), grade III tumours, and tumours with low p27 expression, but these associations did not reach statistical significance. The third tertile had a similar risk as the first tertile. Conclusions: We found that women with low levels of 25OHD3, as compare to women in the middle tertile, had a high risk of breast tumours with an unfavourable prognosis. Highlights: Vitamin D levels below 77 nmol/L was associated with a higher risk of prognostically aggressive tumours as for levels of 77–97 nmol/L. High vitamin D levels may also be associated with an increased risk of relatively unfavourable tumours and have to be validated. Vitamin D levels may be associated only with specific breast cancer sub-groups.